Community legislation on machinery : comments on directive 98/37/EC. (Office for Official Publications of the European Communities, 1999)
In 1993, the Commission published the first version of this document entitled " Community legislation on machinery - Comments on directives 89/392/EEC and 91/368/EEC. This is an updated version, providing further relevant advice on the machinery directive, taking into consideration the practical issues which have been raised during its period of implementation. This document combines the text and the associated comments which are now relevant, from the main directive and its three amendments. The directive has been codified and has become the Directive 98/37 on the approximation of laws of the member states relating to machinery laying down the essential health and safety requirements.